Curricula for students with special educational needs in R. Macedonia and R. Turkey - Nergis Ramo, Akgün; Petrov, Risto; Rashikj Canevska, Olivera; Stanojkovska Trajkovska, Natasha (Faculty of Philosophy, Skopje, 2016)
Special education system is designed to enable education of students with special educational needs. The curricula for children with disabilities are complex need in every educational system. In this paper, we analyzed the primary curricula for five categories of disabilities; intellectual disability; visual impairment, hearing impairment, physical disability and autism; between two countries Republic of Turkey and Republic of Macedonia. Our aim was to represent the curricula in the special education systems and understand the differences between two countries. Our main research question is: What are the differences in curricula for children with special educational needs in R. Macedonia and R. Turkey. In order to be able to provide answer to this question, we had to set 5 associate questions linked with type of disability and country. The result showed that R. Macedonia has 7 compulsory subjects that we can in all special schools, while others are either adopted according to category of disability or available with another title. In Turkey, 16 subjects are the same for all special schools. This qualitative research has theoretical, modern, comparative and descriptive character. We used the method of comparative and descriptive analyzes. The collected data was analyzed according researched questions, giving the appropriate conclusions and suggestions.
Keywords: curricula, programs, students with special educational needs, Republic of Macedonia, Republic of Turkey